PRIMARY OVARIAN PREGNANCY IN A PRIMIGRAVIDA: A CASE REPORT - Agarwal, Mamata; Bai Prabhu T, Radha; R, Niranjana (International Journal of Clinical and Biomedical Research, 2016)
Primary ovarian pregnancy is a rare form of ectopic pregnancy due to the implantation of the gestational sac in the ovary. It is reported to occur in 1 in 25000-40000 pregnancies following natural conceptions and accounts for 0.3- 3% of all ectopic pregnancies. The preoperative diagnosis is difficult and is mostly diagnosed following surgery or histo pathological examination. Here we present a case of ovarian pregnancy which was managed surgically and its review of the literature is discussed. KEYWORDS: Ectopic pregnancy; Extrauterine pregnancy; Primary ovarian pregnancy; Diagnosis; Management.